Soil and farm management effects on yield and nutrient concentrations of food crops in East Africa - Fischer, S.; Hilger, T.; Piepho, H.; Jordan, I.; Karungi, J.; Towett, Erick K.; Shepherd, Keith D.; Cadisch, Georg (Elsevier, 2020)
Crops that grow on soils with higher fertility often have higher yields and higher tissue nutrient concentrations. Whether this is the case for all crops, and which soil and management factors, or combinations mostly affect yields and food nutrient concentrations however, is poorly understood. Here, the main aim was to evaluate effects of soil and management factors on crop yields and food nutrient concentrations in (i) grain, fruit and tuber crops, and (ii) between high and low soil fertility areas.